Transformation and Institutionalization of the Tradition: From Sacig and Cil Paji to Payram in Shor Turks - Ugurcan, Fatma Zehra (Rector CIU Cyprus Int Univ, 2022)
Societies have experienced great changes in 20th and 21st centuries under the influence of industrialization and modernization movements. After a while, they had to add new elements to their culture and eliminate the unsuitable ones, give it a new form or they invented new traditions. Shors, who have lived in Kemerovo region of Southern Siberia for hundreds of years, have also taken their share from this great movement of change. Today there are very few people who continue their ancient traditions and speak Shor language. Changes are also seen in traditional practices and rituals that maintain their existence. Cil Paji and Sacig are one of the recorded and still continuing practices of Shors. Sacig and Cil Paji are traditional practices that have changes, transformed and institutionalized with the change of Shor culture and have become a touristic commodity from time to time. At the beginning of 20th century, an organization called Payram began to be organized. The data used in this study were obtained as a result of interviews with Shor Turks. In addition to this, Russian sources written by the Shor intellectuels were used in order to disseminate and promote the Shor culture. In the study, the practices of Sacig and Cil Paji are mentioned, in addition to these, the organization of Payram is discussed in the context of the invention of tradition. While making the evaluations, the characteristics of these three practices were mentioned and examined within the scope of change, transformation, restructuring, interpretation and invention.
Keywords: Shor Turks; tradition; invention of tradition; ritual; spring rites; Arts & Humanities - Other Topics; Literature